John Bryce, 1834-1913 : the white charger : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, Albany, New Zealand - Cooke, Moyra (Massey University, 2015)
In this thesis I have examined the life of Hon. John Bryce, Native and Defence Minister in the Hall Ministry of 1879-‐82, and Native Minister from 1882 to 1885. Bryce is an important, but substantially unstudied, figure in New Zealand history, who briefly rides his white charger into other people’s stories and then, just as briefly, out again. Accordingly, there are few secondary sources on him, apart from those that cover the two White Charger episodes in his life, the attack at Handley’s Woolshed and the invasion of Parihaka. Of necessity primary sources have played a major part in the research, reports of New Zealand Parliamentary Debates, Appendices to the Journal of the House of Representatives, reports from contemporary newspapers through Papers Past, Waitangi Tribunal Reports, the diary Bryce kept in London in1886, William Rolleston’s diary and correspondence accessed through the Alexander Turnbull Library helped to present a fuller picture of the subject, along with the few available secondary sources. Bryce was a controversial, though respected, figure in his own time, and as mores and attitudes have changed in the century since his death, particularly with reference to race relations, he has been increasingly ‘traduced’ (a word Bryce used, meaning misrepresented), and condemned. To understand Bryce’s perceived ambivalence or hostility towards Maori, this thesis looks at his early life as an immigrant and settler in Wanganui, where events transpired that created lasting impressions and influenced his later responses. The thesis was written chronologically from the time of Bryce’s arrival in New Zealand in 1840, and covers his service with the Kai Iwi Cavalry during Titokowaru’s War, his role as a Wanganui and national politician, his time as Native Minister and a Member of the House of Representatives, until his retirement from politics in 1891. This shows that though Parihaka was an important part of his political life, it did not define or limit his contribution to 19th century politics in New Zealand.
Keywords: John Bryce; New Zealand history; New Zealand politician; Politician biography; 19th century New Zealand; Government and Maori; Parihaka; Wanganui; Colonial history, New Zealand